Brinquedos, Culturas Infantis E Diversidade De Gênero: Uma Análise Sobre A 'Sexta-Feira: Dia Do Brinquedo' Na Educação Infantil - Santos, Paloma Oliveira [UNIFESP] (2018)
This Research Investigates The Gender Relations In The Small Child From The "Friday: Toy Day", In A Public Institution Of Early Childhood Education In The Countryside Of São Paulo. It Seeks To Understand What Values And Norms About Femininities And Masculinities Have Been Imprinted In Toys, How Gender Meanings Have Been Constructed Among Young Children, And How The Institution Organizes This Educational Practice. Through An Ethnographic Research With Girls And Boys Aged 5 And 6, It Reveals Which Types Of Toys Children Have Taken From Home To The Educational Institution Of Early Childhood, Their Choices, Exchanges, And Negotiations, And How Girls And Boys Create Different Gender Meanings In Their Play. The Research Has A Theoretical Reference At The Studies On Toys From The Sociological Approach Of The Childhood, The Childhood Pedagogy, And Gender Studies. Considering The Brazilian Reality, Marked By The Emergence Of Gender Violence In Different Contexts Of Society, And By The Regression In The Field Of Rights